Mechanistic and therapeutic dimensions of DcR3-mediated immunomodulation in sepsis - Abbas, Bilal; Lin, Xinrui; Xu, Chen; Chen, Qi; Su, Jingqian (Frontiers in Immunology, 2026)
Sepsis is a life-threatening syndrome characterized by dysregulated host-immune responses, progressing through hyperinflammatory and immunosuppressive stages. Decoy receptor 3 (DcR3), a soluble member of the TNF receptor superfamily, serves as an immunomodulator in sepsis. Beyond neutralizing FasL, LIGHT, and TL1A to block apoptosis and inflammatory signaling, DcR3 regulates macrophage polarization, dendritic cell maturation, and immune cell survival through its heparan sulfate proteoglycan-binding domain. Evidence from cellular, molecular, and animal studies highlights its dual role in restoring immune balance by modulating both hyperinflammatory and immunosuppressive phases of sepsis. In this review, we summarize current evidence on DcR3 in sepsis and discuss translational challenges and future directions. Current rodent models lacking the TNFRSF6B gene are limited; however, transgenic mice expressing human DcR3 exhibit both protective and detrimental context-dependent effects. Translational challenges include the pharmacokinetics and immunogenicity of recombinant DcR3, although strategies such as PEGylation, nanoparticle encapsulation, and hydrogel delivery may improve its efficacy. Combining DcR3 with PD-1/PD-L1 inhibitors or immunometabolic agents like metformin and dimethyl itaconate presents promising therapeutic potential. Future research will focus on CRISPR/Cas9 knock-in mouse models, multi-omics mapping of DcR3 signaling, and biomarker-guided dosing. Although no DcR3-targeted clinical trials in sepsis have been conducted, DcR3 remains a precision-targeted immunotherapy with mechanistic and translational pathways; this review delineates key knowledge gaps that must be addressed to enable future clinical application.